2013
DOI: 10.1364/ol.38.003061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a dynamical model of a thermally actuated deformable mirror

Abstract: Using the subspace identification technique, we identify a finite dimensional, dynamical model of a recently developed prototype of a thermally actuated deformable mirror (TADM). The main advantage of the identified model over the models described by partial differential equations is its low complexity and low dimensionality. Consequently, the identified model can be easily used for high-performance feedback or feed-forward control. , a TADM has been used to correct static wavefront aberrations. In the above c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…However, since the correction depends on defects on the mirror surface, which do not change over time, the optimal correction must be computed only once and does not need to be adjusted in real-time. To speed up the searches it is possible to take advantage of the measurable time response of the correction [11] and implement model predictive control systems [12].…”
Section: Application To Gw Detectorsmentioning
confidence: 99%
“…However, since the correction depends on defects on the mirror surface, which do not change over time, the optimal correction must be computed only once and does not need to be adjusted in real-time. To speed up the searches it is possible to take advantage of the measurable time response of the correction [11] and implement model predictive control systems [12].…”
Section: Application To Gw Detectorsmentioning
confidence: 99%
“…In the AO system, the control sampling period is T = 2s. This value is chosen on the basis of the step response analysis of the TADM (previously characterized in [26]). This sampling period divides the time t into k discrete time instants, that is, t = kT .…”
Section: Problem Description and Experimental Setupmentioning
confidence: 99%
“…In [26], it has been experimentally demonstrated that TADM can produce variation of essentially the first 9 Zernike coefficients (omitting the piston). We therefore focus on correction of these 9 Zernike coefficients which will be represented by a vector:…”
Section: Problem Description and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations